KAWASAN TUNGKU NAGA DI SAKKOK, SINGKAWANG DRAGON KILN HERITAGE SITE - Sari, Florensita Melly Muspita; Aufa, Naimatul (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Sakkok area in Singkawang is notorious for its traditional Chinese ceramics industry. These ceramics are produced through a wood-firing process in a closed kiln called Dragon Kiln. Dragon Kiln is the product between culture and technology, which was brought by the Southern Chinese immigrants. The only remaining Dragon Kilns, that are still being used and fired now, are in Singapore and Sakkok, Singkawang. Singkawang city is enlisted as Indonesia’s heritage city, therefore, the city is suggested to empower its heritages. This is supported by the people of Singkawang city, in which some of them are the crafters in the Dragon Kiln area. The highlighted architectural problem in this study is “How the architectural design of Dragon Kiln will maximize its Cultural Heritage potential in order to preserve the Dragon Kiln and Traditional Chinese Ceramics Industry?” The applied method for this study is Revitalization Thinking. Revitalization Thinking is a problem solving method based on revitalizing, done in stages, to maximize the design planning. The concept that is implied is an educative, recreational, and sustainable Cultural Heritage Tourism in order to maximize the Cultural Heritage potential of Dragon Kiln through the development of tourism in preserving the Dragon Kiln and Traditional Chinese Ceramics Industry in Singkawang, Indonesia and South-east Asia.